Highly Efficient Nanostructured Bi2WO6 Thin Film Electrodes for Photoelectrochemical and Environment Remediation - Bandar Y. Alfaifi; Hossein Bayahia; Asif Ali. Tahir (Nanomaterials, 2019)
Nanostructured Bi2WO6 thin film electrodes with enhanced solar energy conversion and photocatalytic properties have been fabricated using Aerosol-Assisted Chemical Vapor Deposition (AACVD). By conveniently controlling the deposition process parameters, Bi2WO6 electrodes were fabricated with nanoplates and hierarchical buckyball-shaped microsphere structures morphology. A detailed study has been conducted to correlate the structure and morphology with the photoelectrochemical (PEC) and photocatalytic dye degradation performance. The PEC investigations revealed that the hierarchical buckyball-shaped microsphere structured Bi2WO6 electrodes have shown the photocurrent density of 220 μAcm−2 while nanoplates have a photocurrent density of 170 μAcm−2 at 0.23 V (vs. Ag/AgCl/3M KCl) under AM1.5 illumination. The PEC characterization of Bi2WO6 electrodes also reveals that the photocurrent density and photocurrent onset potential is strongly dependent on the orientation and morphology, hence the deposition parameters. Similarly, the methylene blue (MB) and rhodamine B (RhB) photodegradation performance of Bi2WO6 electrodes also show a strong correlation with morphology. This finding provides an appropriate route to engineer the energetic and interfacial properties of Bi2WO6 electrode to enhance solar energy conversion and the photocatalytic performance of semiconductor materials.